'I hope he goes first': Exploring determinants of engagement in future planning for adults with a learning disability living with ageing parents. What are the issues?. (15th April 2012) - Bibby, Rita
<x xml:space="preserve">Abstract</x> Accessible Summary This paper attempts to find out why it is that many adults with a learning disability and their older parents and carers do not make plans for their future. The author takes a look at other research to try and find the reasons for why this is. The author finds that this may be to do with the type of relationship families have with professionals and if they feel able to trust them. The author suggests ways to improve these relationships. Summary This paper reports on the key findings from a review of the literature on future planning for adults with a learning disability who live with older parents and carers. This area has gained attention in recent years, owing to the improved life expectancy of people with a learning disability and the increasing number who now outlive their parents. For those currently living with older parents and carers, this has major implications for the future, with the likelihood that formal services will eventually take over the care role. It is suggested that the presence of a plan for the future, formulated at a time of stability and in advance of any crisis, may lead to improved outcomes for this next phase of life. However, regardless of several policy initiatives to encourage active planning for the future, the take‐up rate remains poor. This review of the literature seeks to offer an explanation for this through identifying the barriers to future planning as experienced by people with a learning disability and their older carers. The evidence suggests that there are ten key barriers to engagement in future planning. Consideration is given to each of these in turn, and a common thread is identified, that of the quality of the relationships between the families and the professionals who they come into contact with. Gaps in the research are considered, and the need for further work identified to reflect the views of black and minority ethnic families and so‐called hidden families who are not known to statutory services. Also highlighted is the lack of participation in the research of those people with more severe disabilities who use alternative methods of communication.